2013
DOI: 10.1186/1471-2334-13-466
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of Klebsiella pneumoniaeST14 carrying CTX-M-15 causing neonatal sepsis in Tanzania

Abstract: BackgroundKlebsiella pneumoniae strains expressing ESBLs are a predominant cause of hospital acquired infections. Here we describe the molecular epidemiology of these isolates in a tertiary hospital in Tanzania, as potential pathogens for neonatal infections.MethodsBetween April 2009 and March 2010 all Klebsiella pneumoniae isolates with phenotypic expression Extended Spectrum Beta Lactamase (ESBL) were collected and characterized. Identification was done using in house biochemical tests in case of ambiguous r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
84
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 30 publications
7
84
2
2
Order By: Relevance
“…[20]. Also in Tanzania, in a study on neonatal sepsis, 50.3% of the K. pneumoniae were found to be ESBL producers [13]. Importantly, a much more recent study in India (2014) in a nephrourology teaching institute showed that among Enterobacteriaceae isolated from blood cultures, 39.6% were ESBL producers [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[20]. Also in Tanzania, in a study on neonatal sepsis, 50.3% of the K. pneumoniae were found to be ESBL producers [13]. Importantly, a much more recent study in India (2014) in a nephrourology teaching institute showed that among Enterobacteriaceae isolated from blood cultures, 39.6% were ESBL producers [21].…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia (2009), E. coli was isolated from 18.7% of the cases (67/359) in clinical samples of both hospitalized and non-hospitalized patients, of which 35.8% (24/67) were ESBL producers [12]. In Tanzania (2009-2010), 50.3% (92/183) of K. pneumoniae strains isolated from blood cultures were ESBL producers; 5.5% (5/92) of them were from the community and 94.5% (87/92) from hospitals [13]. In Ghana (2007) and Mali (2003), ESBLs were produced, respectively, by 49.4% and 63.4% of Enterobacteriaceae isolated in community and hospital samples [14,15] [16].…”
Section: Introductionmentioning
confidence: 99%
“…showed that bla CTX-M 15 was localized on a plasmid of 25 to 485KB and that ST14 and ST48 clones carried also resistance genes to gentamicin and trimethoprim-sulfamethoxazole [56]. More recently, in a study in Central African Republic, Rafai et al showed that all ESBL producing Klebsiella pneumoniae isolated from surgical wounds, expressed bla CTX-M 15 and aac(6 H)-Ib-cr [58].…”
Section: Discussionmentioning
confidence: 99%
“…In Tanzania high mortality has been observed with infections associated with ESBL producing gram negative bacteria (Kayange et al, 2010). In our setting, high prevalence of health care associated infections due to ESBL producing Klebsiella pneumoniae have been observed in surgical wards and neonatal units (Mshana et al, 2013). Pseudomonas spp also have been found to be common causes of wound infections in our setting (Mbunda et al, 2012).…”
mentioning
confidence: 82%